Ezetimibe Promotes Brush Border Membrane-to-Lumen Cholesterol Efflux in the Small Intestine - Nakano, Takanari; Inoue, Ikuo; Takenaka, Yasuhiro; Ono, Hiraku; Katayama, Shigehiro; Awata, Takuya; Murakoshi, Takayuki (PLOS ONE, 2016)
Ezetimibe inhibits Niemann-Pick C1-like 1 (NPC1L1), an apical membrane cholesterol transporter of enterocytes, thereby reduces intestinal cholesterol absorption. This treatment also increases extrahepatic reverse cholesterol transport via an undefined mechanism. To explore this, we employed a trans-intestinal cholesterol efflux (TICE) assay, which directly detects circulation-to-intestinal lumen 3H-cholesterol transit in a cannulated jejunal segment, and found an increase of TICE by 45%. To examine whether such increase in efflux occurs at the intestinal brush border membrane(BBM)-level, we performed luminal perfusion assays, similar to TICE but the jejunal wall was labelled with orally-given 3H-cholesterol, and determined elevated BBM-to-lumen cholesterol efflux by 3.5-fold with ezetimibe. Such increased efflux probably promotes circulation-to-lumen cholesterol transit eventually; thus increases TICE. Next, we wondered how inhibition of NPC1L1, an influx transporter, resulted in increased efflux. When we traced orally-given 3H-cholesterol in mice, we found that lumen-to-BBM 3H-cholesterol transit was rapid and less sensitive to ezetimibe treatment. Comparison of the efflux and fractional cholesterol absorption revealed an inverse correlation, indicating the efflux as an opposite-regulatory factor for cholesterol absorption efficiency and counteracting to the naturally-occurring rapid cholesterol influx to the BBM. These suggest that the ezetimibe-stimulated increased efflux is crucial in reducing cholesterol absorption. Ezetimibe-induced increase in cholesterol efflux was approximately 2.5-fold greater in mice having endogenous ATP-binding cassette G5/G8 heterodimer, the major sterol efflux transporter of enterocytes, than the knockout counterparts, suggesting that the heterodimer confers additional rapid BBM-to-lumen cholesterol efflux in response to NPC1L1 inhibition. The observed framework for intestinal cholesterol fluxes may provide ways to modulate the flux to dispose of endogenous cholesterol efficiently for therapeutic purposes.